2020
DOI: 10.1007/s00707-020-02860-y
|View full text |Cite
|
Sign up to set email alerts
|

Doppler effect described by the solutions of the Cattaneo telegraph equation

Abstract: The Cattaneo telegraph equation for temperature with moving time-harmonic source is studied on the line and the half-line domain. The Laplace and Fourier transforms are used. Expressions which show the wave fronts and elucidate the Doppler effect are obtained. Several particular cases of the considered problem including the heat conduction equation and the wave equation are investigated. The quasi-steady-state solutions are also examined for the case of non-moving time-harmonic source and time-harmonic boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We expect that further analysis of wave phenomena seen in solutions to the Cattaneo equation, like the Doppler studied recently in Ref. [72], will appear helpful to understand better wave properties of solutions to the generalized Cattaneo equation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We expect that further analysis of wave phenomena seen in solutions to the Cattaneo equation, like the Doppler studied recently in Ref. [72], will appear helpful to understand better wave properties of solutions to the generalized Cattaneo equation.…”
Section: Discussionmentioning
confidence: 86%
“…(x, ξ) = L −1 [F (x, z); ξ]. This inverse Laplace transform can be calculated by using the formulas placed in [71, Appendix A] and/or[72, Appendix B]. Namely,L −1 [(z 2 − λ 2 ) −1/2 exp[− |x| a (z 2 − λ 2 ) 1/2 ]; ξ} = Θ(ξ − |x| a )I 0 [ 1 2τ (ξ 2 − x 2 a 2 ) 1/2 ] (C2) and L −1 [z(z 2 − λ 2 ) −1/2 exp[− |x| a (z 2 − λ 2 ) 1/2 ]; ξ} = δ(ξ − |x| a ) + Θ(ξ − |x| a )…”
mentioning
confidence: 99%
“…(vi) When n 0 0, n 1 1, χ 0 > 1 and 0 < χ 1 < 1, we obtain the half-space solution of the modified hyperbolic DPL. It is found that for copper the ratio χ 1 0.246 [12], which yields that χ 2 1 0.06 not 0.5 as in the original hyperbolic DPL, refer to (22).…”
Section: Numerical Results and Discussionmentioning
confidence: 95%
“…Furthermore, the generalized variational principles for the Fourier, MCV, parabolic DPL, two-temperature, and Guyer-Krumhansl heat conduction models have been obtained using the Laplace transform and employed to approximate analyses based on the Rayleigh-Ritz method by Li and Cao [18,19]. We refer the reader to the recent works on the MCV telegraph equation and its generalizations which have investigated its connection with continuous-time random walk scheme and its conditional solutions [20,21], the Doppler effect [22], and the integral decomposition [23].…”
Section: Introductionmentioning
confidence: 99%
“…Effectively, since analytical solutions are impossible, the study method is of the Monte Carlo type. Note that the analytical solution elucidating the Doppler effect in the subsonic range of the second sound in a homogeneous 1d medium has recently been obtained [15].…”
Section: Problem Formulationmentioning
confidence: 99%